Chapter 12 The role of mobility and transnationality for local marketplaces - Menet, Joanna (Taylor & Francis, 2023)
Dominant representations depict outdoor markets in Switzerland and beyond as typically local. Not only are they presented and promoted by different actors as being local in terms of the products sold on a market day, but also the traders are imagined as being locals. Applying a 'mobility lens', this chapter looks at marketplaces at the intersections of mobile traders, performance of local anchorage and mobilization of transnational networks. Starting from fieldwork on two markets in Switzerland, this chapter explores how the local character of outdoor markets is produced by different market participants such as customers, farmers, vendors and local authorities. We delve into the different meanings of 'local' and show that locality is entwined with mobility and transnationality. We illustrate that mobility, transnationality and nationalism play a crucial role for the economic success of markets and suggest that vendors are embedded in a global identity politics. Thus, we argue that markets can be analysed as expressions of national forms of identification.